2019
DOI: 10.1111/aec.12825
|View full text |Cite
|
Sign up to set email alerts
|

Spatial niche modelling of five endemic cacti from the Brazilian Caatinga: Past, present and future

Abstract: Climate change, together with human activities, impacts on natural and human systems on all continents and poses a major threat to biodiversity, especially in environments with a high rate of endemism and where species are profoundly adapted to specific environmental conditions, as is the case of the seasonally dry tropical forests, noticeably the Caatinga, an exclusively Brazilian biome. The objective of this study was to build spatial niche models of five species of Cactaceae (Arrojadoa penicillata, Brasilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
1
8
0
6
Order By: Relevance
“…De acordo com esses autores, fatores como disponibilidade de recursos, condições edafoclimáticas, perturbações antrópicas ou naturais, interferem na estrutura e dinâmica vegetal e, consequentemente, as populações de C. jamacaru. Estudos recentes têm apontado os impactos das mudanças climáticas e o uso forrageiro como os principais fatores que afetam a distribuição de cactáceas endêmicas da Caatinga e, a médio e longo prazo, algumas espécies apresentarão grande risco de extinção, enquanto que outras apresentarão uma queda na distribuição em seus habitats (Simões et al, 2019;Carvalho, 2016). Assim, estudos como este com Cactaceae que ocorrem na Caatinga são incentivados para entender o estabelecimento e as chances de sobrevivência dessas espécies no seu ambiente natural, sobretudo, diante de um cenário de mudanças climáticas e intervenções antrópicas.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…De acordo com esses autores, fatores como disponibilidade de recursos, condições edafoclimáticas, perturbações antrópicas ou naturais, interferem na estrutura e dinâmica vegetal e, consequentemente, as populações de C. jamacaru. Estudos recentes têm apontado os impactos das mudanças climáticas e o uso forrageiro como os principais fatores que afetam a distribuição de cactáceas endêmicas da Caatinga e, a médio e longo prazo, algumas espécies apresentarão grande risco de extinção, enquanto que outras apresentarão uma queda na distribuição em seus habitats (Simões et al, 2019;Carvalho, 2016). Assim, estudos como este com Cactaceae que ocorrem na Caatinga são incentivados para entender o estabelecimento e as chances de sobrevivência dessas espécies no seu ambiente natural, sobretudo, diante de um cenário de mudanças climáticas e intervenções antrópicas.…”
Section: Resultsunclassified
“…As mudanças climáticas, juntamente com as atividades humanas, impactam os ecossistemas naturais em todos os continentes e representam uma grande ameaça à biodiversidade, especialmente em ambientes com alto índice de endemismo e onde as espécies são profundamente adaptadas às condições ambientais específicas, como é o caso das florestas tropicais sazonalmente secas, notavelmente a Caatinga, um bioma exclusivamente brasileiro (Simões et al, 2019). As condições edafoclimáticas da Caatinga favorecem o desenvolvimento de espécies vegetais bem adaptadas à região (Souza et al, 2019), a exemplo das cactáceas, que apresentam características adaptativas singulares em áreas com déficit hídrico e elevada amplitude térmica.…”
Section: Introductionunclassified
“… Silva et al (2019) showed that, throughout the Caatinga biome, areas of suitable habitat for endemic plant species would be reduced under both optimistic and pessimistic future climate change scenarios. Simoes et al (2019) found that endemic cacti species are threatened with extinction due to the retraction of environmentally suitable areas. This area reduction for plants in STDFs was also reported in other works ( Oyama & Nobre, 2003 ; De Andrade et al, 2017 , Marengo, Torres & Alves, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this region is home to sites of interest for establishing new areas of integral protection due to extensive natural remnants ( MMA, 2021 ; Antongiovanni, Venticinque & Fonseca, 2018 ; Antongiovanni et al, 2020 ). The south of the Caatinga is fundamental for the conservation of cacti species ( Carvalho et al, 2022 ) and one of the few areas in eastern Brazil capable of safeguarding different Cactaceae species in climate change scenarios in the next 60 years ( Simoes et al, 2019 ). The east and central parts are also crucial for conserving endemic plants from the Caatinga dry forest ( Silva et al, 2019 ), corroborating the pattern found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…If the climate changes permanently, this will affect the ecological niche of species in this environment (e.g. Chagas et al 2020;Silva et al 2020;Simões et al 2020).…”
Section: Introductionmentioning
confidence: 99%